Mathematical modeling of snow drifts transport by wind over the mountain terrain - Mahmoud Zarrini (Journal of Hyperstructures, 2013)
In this paper, estimation of snow particles motion velocity and snow-drift density by mathematical modeling is studied. The snow particles flow is modeling from fluid dynamic concepts and micro-continuum approach (couple stresses fluid [1]). The present approach is compared to conventional classical approach of logarithmic law of snow-drift density ([2], [3]). It is shown that, the present approach yield better results than that of conventional approach.